Business model, case: California Interiors - Barbuzón Pacheco, María Olivia (Universidad de Sonora, 2017)
Currently, companies are immersed in an environment of open markets, for which they are forced to operate with excellent quality and to ensure that this is a constant norm. For which they require a reliable and solid support to organize and take advantage of their resources and be more competitive every day. The administration together with the internal accounting department play a very important for the success of any company, which is a fundamental tool, it is a means in which it allows us to evaluate the development of the organization and detect opportunities to improvement. This document allows a real evaluation of the business opportunity, identify assumptions for success; provide the possibility to explain, justify, project and evaluate the basic assumptions of the business. Give the entrepreneur the first administrative tool for your company. In addition to exposing in detail the organizational structure of the company, noting the positions and the relationship that exists between them. Explain the hierarchy, the degrees of authority and responsibility, the functions and activities of the organic units or departments that comprise it to define responsibilities, avoid duplication of functions and detect omissions. Currently, a large number of social organizations have adopted the use of the Business Model, as a means to satisfy different types of needs, as well as to define resource requirements of all kinds, in a time frame and ways to attainment of them. Its substantial objective is to promote the best use of human and material resources, by establishing short and long-term goals and objectives, evaluating the current and future status of the company and the environment in which it will operate.